Coffee consumption and cardiovascular health in the general population. (3rd October 2022) - Wenzel, J; Senftinger, J; Borof, K; Ojeda, F; Aarabi, G; Beikler, T; Mayer, C; Behrendt, C; Walther, C; Zyriax, B C; Twerenbold, R; Blankenberg, S; et al.
Abstract: Background: Coffee, next to water the most widespread beverage, is attributed both harmful and protective characteristics concerning cardiovascular health. This study aimed to evaluate associations of coffee consumption with cardiac biomarkers, echocardiographic, and electrocardiographic parameters as well as major cardiovascular diseases. Methods and results: We performed a cross-sectional analysis of 9, 009 participants a large German population-based cohort study, enrolled between 2016 and 2018 median age 63 [IQR: 55; 69] years. Coffee consumption was classified into three groups: <3 cups/day (low), 3–4 cups/day (moderate), >4 cups/day (high). In linear regression analyses adjusted for age, sex, body mass index, diabetes, hypertension, and smoking, moderate and high coffee consumption were associated with LDL-cholesterol (β=2.08; 95% CI: 0.14, 4.03, p=0.036; β=5.69; 95% CI: 2.91, 8.47; p<0.001). Moderate and high coffee consumption were negatively associated with systolic (β=−1.6; 95% CI: −2.66, −0.54; p=0.003; β=−2.63; 95% CI: −4.15, −1.12; p=0.001) and diastolic blood pressure (β=−0.8; 95% CI: −1.38, −0.22; p=0.007; β=1.28; 95% CI: −2.11, −0.45; p=0.002). Different levels of coffee consumption did neither correlate with any investigated electrocardiographic or echocardiographic parameter nor with prevalent major cardiovascular diseases, including prior myocardial infarction and heart failure. Conclusions: In this cross-sectional analysis, moderate and high coffee consumption was positively associated with LDL-cholesterol and negatively associated with systolic and diastolic blood pressure. However, major cardiovascular diseases including heart failure and its diagnostic precursors were not associated with coffee consumption, connoting a neutral role of coffee in the context of cardiovascular health. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Deutsche Forschungsgemeinschaft [Grant Number TH1106/5-1; AA93/2-1]The Foundation Leducq [Grant Number 16 CVD 03]